Association of UGT1A1*6, UGT1A1*28, or ABCC2 c.3972C>T genetic polymorphisms with irinotecan‐induced toxicity in Asian cancer patients: Meta‐analysis. Issue 7 (31st May 2022) - Atasilp, Chalirmporn; Biswas, Mohitosh; Jinda, Pimonpan; Nuntharadthanaphong, Nutthan; Rachanakul, Jiratha; Hongkaew, Yaowaluck; Vanwong, Natchaya; Saokaew, Surasak; Sukasem, Chonlaphat
Abstract: Effects of UGT1A1 *6 and UGT1A1 *28 genetic polymorphisms on irinotecan‐induced severe toxicities in Asian cancer patients are inconclusive. Also, ABCC2 c.3972C>T may affect toxicity of irinotecan. The aim was to assess the aggregated risk of neutropenia or diarrhea in Asian cancer patients taking irinotecan and inherited UGT1A1*6, UGT1A1*28, or ABCC2 c.3972C>T genetic variants. A PubMed literature search for eligible studies was conducted. Odds ratios (ORs) were measured using RevMan software where p values <0.05 were statistically significant. Patients that inherited both UGT1A1*6 and UGT1A1*28 genetic variants (heterozygous: UGT1A1*1/*6 + *1/*28 and homozygous: UGT1A1*6/*6 + *28/*28 ) were significantly associated with increased risk of neutropenia and diarrhea compared to patients with UGT1A1*1/*1 (neutropenia: OR 2.89; 95% CI 1.97–4.23; p < 0.00001; diarrhea: OR 2.26; 95% CI 1.71–2.99; p < 0.00001). Patients carrying homozygous variants had much stronger effects in developing toxicities (neutropenia: OR 6.23; 95% CI 3.11–12.47; p < 0.00001; diarrhea: OR 3.21; 95% CI 2.13–4.85; p < 0.00001) than those with heterozygous variants. However, patients carrying the ABCC2 c.3972C>T genetic variant were not significantly associated with neutropenia (OR 1.67; 95% CI 0.98–2.84; p = 0.06) and were significantly associated with a reduction in irinotecan‐induced diarrhea (OR 0.31; 95% CI 0.11–0.81; p = 0.02). Asian cancer patients should undergo screening for both UGT1A1*6 and UGT1A1*28 genetic variants to reduce substantially irinotecan‐induced severe toxicities.